Increasing incidence of aortic aneurysms in England and Wales. Issue 6665 (7th January 1989) - Fowkes, F. G.; Macintyre, C. C.; Ruckley, C. V.
Abstract : The numbers of patients being admitted to hospital with aortic aneurysms have increased recently. A study was carried out to try to find out whether this was a true increase in incidence or whether it could be attributable to more accurate diagnosis and better surgical techniques. From analyses of routine statistics it was found that from 1950 to 1984 age standardised mortality rose 20-fold in men to 47.1 per 100, 000 population and 11-fold in women to 22.2 per 100, 000 and that this was mainly due to more deaths from abdominal aneurysms. Hospital admissions of men with abdominal aneurysms were found to have increased steadily from 1968 to 1983, but the increase for women admitted did not begin until 1978. An increase in both emergency and elective admissions and only a marginal fall in deaths in hospital (from 45% to 39%) suggest that admissions for abdominal aneurysms increased across a wide range of severity of disease. It is concluded for the following reasons that the true incidence of aortic aneurysms, particularly abdominal aneurysms, has been increasing in England and Wales: the trends are not wholly compatible with advances in diagnosis and surgery, there are inconsistencies by age and sex, and increases have occurred in the number of complicated as well as uncomplicated cases.